Clinical characteristics of myelin oligodendrocyte glycoprotein antibody-associated disease according to their epitopes - Seok, Jin Myoung; Jeon, Mi Young; Chung, Yeon Hak; Ju, Hyunjin; Lee, Hye Lim; Kwon, Soonwook; Min, Ju-Hong; Kang, Eun-Suk; Kim, Byoung Joon (Frontiers in Neurology, 2023)
Background The detection of myelin oligodendrocyte glycoprotein autoantibodies (MOG-Ab) is essential for the diagnosis of MOG-Ab-associated disease (MOGAD). The clinical implications of different epitopes recognized by MOG-Ab are largely unknown. In this study, we established an in-house cell-based immunoassay for detecting MOG-Ab epitopes and examined the clinical characteristics of patients with MOG-Ab according to their epitopes. Methods We conducted a retrospective review of patients with MOG-Ab-associated disease (MOGAD) in our single center registry, and collected serum samples from enrolled patients. Human MOG variants were generated to detect epitopes recognized by MOG-Ab. The differences in clinical characteristics according to the presence of reactivity to MOG Proline42 (P42) were evaluated. Results Fifty five patients with MOGAD were enrolled. Optic neuritis was the most common presenting syndrome. The P42 position of MOG was a major epitope of MOG-Ab. The patients with a monophasic clinical course and childhood-onset patients were only observed in the group that showed reactivity to the P42 epitope. Conclusion We developed an in-house cell-based immunoassay to analyze the epitopes of MOG-Ab. The P42 position of MOG is the primary target of MOG-Ab in Korean patients with MOGAD. Further studies are needed to determine the predictive value of MOG-Ab and its epitopes.